Infantile hemangioma status by dynamic infrared thermography: A preliminary study. (8th April 2016) - Burkes, Shoná A.; Patel, Manish; Adams, Denise M.; Hammill, Adrienne M.; Eaton, Kenneth P.; Randall Wickett, R.; Visscher, Marty O.
Abstract: Background: Infantile hemangiomas (IH) are initially warm due to increased proliferation and perfusion then involute with apoptosis and reduced perfusion. Objective quantitative evaluation of IH treatment response is essential for improving outcomes. We applied a functional imaging method, dynamic infrared (IR) thermography, to investigate IH status versus control skin and over time. Materials and methods: A preliminary prospective observational study was conducted among 25 subjects with superficial or mixed IHs (< 19 months) over 59 clinic visits. Infrared images of IHs and control sites, standardized color images, and three‐dimensional images were obtained. Tissue responses following application and removal of a cold stress were recorded with video IR thermography. Outcomes included areas under the curve during cooling (AUCcool ) and rewarming (AUCrw ) and thermal intensity distribution maps. Results: AUCcool and AUCrw were significantly higher and cooling rate slower for IHs versus uninvolved tissue indicating greater heat, presumably due to greater perfusion and metabolism for the IH. IR distribution maps showed specific areas of high and low temperature. Significant changes in IH thermal activity were reflected in the difference (AUCcool – AUCrw ), with 6.2 at 2.2 months increasing to 37.6 at 12.8 months. IH cooling rate increased with age, indicating slower recovery, and interpreted as reduced proliferation and/or involution. Conclusions: Dynamic IR thermography was a well‐tolerated, quantitative functional imaging modality appropriate for the clinic, particularly when structural changes, i.e., height, volume, color, were not readily observed. It may assist in monitoring progress, individualizing treatment, and evaluating therapies. Clinical Trial Registration:www.clinicaltrials.gov (Identifier NCT02061735)